Potential of lignocellulosic materials (wood and bark) from Ateleia glazioviana and Hovenia dulcis as a natural wood preservative - M. Talgatti; T. Baldin; S. M. V. Nunes; T. L. Dias; E. E. P. Baraúna; E. J. Santini; G. Valcorte; R. R. Roubuste; P. D. C. Silva (Brazilian Journal of Biology)
Abstract The lignocellulosic materials of some plant species are rich in chemical compounds that can serve as a source of natural and environmentally less aggressive biocides for treating wood. The aim of this study was to verify the potential of the lignocellulosic materials (wood and bark) of Ateleia glazioviana and Hovenia dulcis as a natural wood preservative. The extracts were prepared by heating the materials to 100 °C at a concentration of 10%. The wood samples were treated in a laboratory autoclave using the empty cell method. Control samples (untreated) and samples treated with chromated copper borate - CCB (2.5%) were used as a comparison. The accelerated rot test in the laboratory was carried out using a sample of the colony of the white rot fungus, Trametes versicolor. Mass loss, solubility in 1% NaOH, scanning electron spectroscopy (SEM) and attenuated total reflection infrared spectroscopy (ATR-FTIR) were evaluated. A rotting field test was also carried out in a forest fragment for 180 days and the mass loss, apparent specific mass, ATR-FTIR, and dynamic bending of the wood samples were evaluated. In laboratory tests, natural extractive solutions from the bark and wood of Hovenia dulcis and only from the bark of Ateleia glazioviana have fungitoxic potential against the white rot fungus, when compared to material without preservative impregnations. The resistance of the wood in the field to rot did not obtain significant results with the application of the natural preservatives, and future studies will need to increase the concentration of the extracts in an attempt to improve their performance as natural biocides.